2019
DOI: 10.11648/j.ss.20190806.20
|View full text |Cite
|
Sign up to set email alerts
|

Life Expectancy, Public Health Spending and Economic Growth in Nigeria

Abstract: The paper examines the link between life expectancy, public health spending and economic development in Nigeria for the period 1995 to 2017. Data used were life expectancy at birth, public health expenditure and the gross domestic product (GDP) sourced from the World Bank data. Situational analysis, Ordinary Least Square and the granger causality test techniques were employed. The situational analysis showed that the trend of GDP and expectancy were upward while health expenditure had an irregular trend. The O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
3
3
0
Order By: Relevance
“…On the other hand, if the physicians are poorly trained and less skilled, government will have to spend significant resources either for re-training or recruitment of better qualified health personnel. This result is in line with the findings by [55].…”
Section: Three Stage Least Squares (3sls) Results For Public Expendit...supporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, if the physicians are poorly trained and less skilled, government will have to spend significant resources either for re-training or recruitment of better qualified health personnel. This result is in line with the findings by [55].…”
Section: Three Stage Least Squares (3sls) Results For Public Expendit...supporting
confidence: 93%
“…This means that there is a bi-directional causal relationship between public health expenditure and health status. This evidence is similar to Ibikunle [55] who found a bidirectional relationship between life expectancy as a measure of health outcomes and healthcare spending; but it's in contrast to some other studies such as Obienyi et al, [53]; Nwani and Kelikume [56].…”
Section: Discussion Of Empirical Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This implied that a rise in government spending on healthcare significantly influences the per capita GDP of a country. Similarly, Ibikunle (2019) obtained similar results and concluded that increased government spending on the health sector should be prioritized to realize the sustainable development goal of economic growth. The study employed the use of the ordinary least square (OLS) and the Granger causality post‐estimation approach to examine the influence of healthcare expenditure on the growth of GDP.…”
Section: Literature Reviewmentioning
confidence: 81%
“…In addition, the longevity of life is enhanced by adequate health expenditure. Ogungbenle et al (2013) found no association between LEXP and GDP in Nigeria. Sede and Ohemeng (2015) had an unconventional result by showing that the unemployment and exchange rates are the factors that impact LEXP positively and not per capita income.…”
Section: Literature Reviewmentioning
confidence: 96%